Knowledge, attitude and awareness towards the usage of halal medical devices in Shah Alam, Selangor / Noorul Huda Sahari ... [et al.] - Sahari, Noorul Huda; Muhamad Fauzi, Amirah Zulaikha; Harun, Nur Hafizah; Mazlan, Farhaneen Afzal (Universiti Teknologi MARA, 2021)
The halal industry nowadays not only covers the food industry, but has expanded to logistics, consumer goods, cosmetics, and pharmaceutical industries. Halal medical device industry players started to request the certification for medical devices in 2013 to make the products accepted in Muslim countries, thus expanding the marketability of the product worldwide. With the addition of medical devices as one of the latest schemes that can be applied for the halal certificate, this study aims to investigate the knowledge, attitude and awareness among Muslim society towards the usage of halal medical devices in Shah Alam, Selangor. This study adopted a quantitative method to collect the data. The data collected were analysed for Descriptive Statistics and Correlation Analysis by using the SPSS. All the items in the questionnaire were analysed with Reliability Testing (Cronbach Alpha) to test for their reliability. The findings of this research showed that all the independent variables in this study, which were knowledge attitude and the awareness level have a significant relationship with the dependent variable, which was the usage of halal medical devices. Besides, the correlation analysis showed that knowledge, attitude, and awareness are positively correlated with the usage of halal medical devices. However, the awareness level has the lowest positive correlation relationship with the usage of halal medical devices, indicating that Muslim's consumer awareness is still low. Therefore, this study recommended that both stakeholders, whether the government or the halal authority may increase the awareness level on a halal medical device for Muslim consumers by campaign promotion as the demands are increasing with the growth of the industry.